Is anuria prior to pediatric renal transplantation associated with poor allograft outcomes?. (8th May 2019) - Alam, Zaheer; VanderBrink, Brian A.; Brewer, Nathalie; Hooper, David; Tiao, Greg; Alonso, Maria; Nathan, Jaimie; DeFoor, W. Robert; Sheldon, Curtis; Reddy, Pramod P.
Abstract: Introduction: Anuria from end‐stage renal disease leads to a defunctionalized bladder and may pose technical challenges at the time of renal transplantation. Anuria's effect on bladder function after renal transplantation is considered to be minimal in adults, although a paucity of evidence is available in children. The purpose of this study was to examine the effects of anuria prior to pediatric renal transplantation for ESRD due to medical renal disease on allograft outcome. Methods: We performed a retrospective review of pediatric patients who underwent renal transplantation for medical renal disease at our institution between 2005 and 2016. Demographics and clinical data were assessed. We also compared GFR at 1 year post‐transplant for medical renal patients with history of anuria and those without. Results: Twenty‐one patients fulfilled our inclusion criteria with median duration of anuria was 10 months. Preoperative VCUG was available in five patients and their bladder capacity was 29% of expected bladder capacity for age (range 8%‐41%). Anticholinergic therapy was prescribed in six patients (28%) for a mean duration of 5 months (range 1‐16 months). Comparison of GFR at 1 year post‐transplant in anuria group and those without anuria showed no difference (69 vs 75 mL/min, P = 0.37). No correlation was observed between duration of anuria and post‐transplant GFR. Conclusion: The majority of children in our pretransplant anuria cohort did not develop bladder dysfunction after renal transplantation. No difference was observed between GFR at 1 year when comparing anuric to non‐anuric transplant recipients of medical renal disease etiology.